Disperse Dyes as Corrosion Inhibitors for Aluminum Alloy in Trichloroacetic Acid System - S. DESAI, PIYUSH; VASHI, R.T. (Asian Journal of Chemistry, 2010)
The corrosion of aluminum alloy in trichloroacetic acid containing disperse dyes has been studied. In trichloroacetic acid (TCA), the corrosion rate increases with the acid concentration. At constant acid concentration, the inhibition efficiency of dyes increases with the inhibitor concentration. Similarly, at constant inhibitor concentration, the inhibition efficiency decreases with the increase of acid concentration. In 0.01 M trichloroacetic acid for 24 h immersion period, at 4 mM inhibitor concentration the inhibition efficiency of inhibitors increases in the order: coralene violet 3R Ex (C.I. disperse violet 99) (95.80 %) < coralene yellow Br. REL (C.I. disperse orange 61) (91.98 %). As temperature increases, percentage of inhibition increases in coralene violet 3R Ex and coralene yellow Br. REL almost in all case. Plot of log (θ /1- θ) vs. log C results in a straight line suggest that the inhibitors cover both the anodic and cathodic regions through general adsorption following Langmuir isotherm. The curves show little anodic but significant cathodic polarization.